Social relations and employees' rejection of working from home: A social exchange perspective - Alexandra Mergener; Miriam Trübner (New Technology, Work and Employment, 2022)
Why do employees prefer working on-site rather than working from home (WfH)? This article examines how personal concerns at the level of social relationships affect rejection of WfH. Using a large-scale representative survey of employees in Germany (N0.167em=0.167em4448), we apply logistic regression analyses to examine, first, the association between employees' social relationships at work and rejection of WfH and, second, the moderating effects of social relations in the private sphere. Results indicate that the quality of the working atmosphere with colleagues and the supervisor is a motive for rejecting WfH, more so for people living alone than for couples and families. Changes in working culture due to widespread use of new technology and digital mobile devices and, not least, the extensive experiences with WfH during the Covid-19 pandemic, highlight the relevance of considering employees' workplace preferences in future research.
Keywords: 330; living arrangements; logistic regression; remote work; SET; social exchange theory; social integration; WfH; working from home